HEALTHY LIFESTYLE BEHAVIOR FOR WORKERS IN CONSTRUCTION SERVICES - Yasinta Indah Widyaningsih; Yuliani Setyaningsih; Syamsulhuda B.M. (Jurnal Akuntansi dan Pajak, 2023)
Healthy lifestyle behavior in the workplace is empowering workers to know, be willing and able to practice a healthy lifestyle in their daily life and to take an active role in creating a healthy workplace to maintain, maintain and maintain the health of workers to stay healthy and productive. This study aims to describe the effectiveness of the application of several health promotion methods on healthy lifestyle behaviors in workers in an effort to prevent and control diseases in the workplace, especially in companies engaged in construction services. The design in this study uses a systematic literature review by identifying, collecting and evaluating data from Google Scholar, Science Direct, Research Gate, Sinta and Pubmed. The results show that if the application of health promotion methods using safety talk and peer as change agents is effective in influencing healthy lifestyle behavior of workers in construction services. The more effective the respondents in participating in safety talks and peer as change agents, the more indicators of healthy lifestyle behavior that can be achieved. Keywords: safety talk, peer as change agent, healthy lifestyle behavior, construction workplace